Availability and use of information communication technology in research institutes in Oyo state, Nigeria (2013)
This research work examined the availability and use of information and communication technologies by researchers in research institutes in Oyo State, Nigeria. The study aimed at determining the personal characteristics of the respondents, identified the information communication technologies (ICTs) available in the research institutes, the usage pattern of ICT facilities by researchers and activities for which ICT resources are used. The population of the study was three hundred and thirty-seven (337) researchers and the data collection instrument used was questionnaire. The study confirmed the availability of some ICT facilities such as Computer, mobile phones, internet, Scanners, DVD, and CD ROM. The study also revealed that fax and telex were the least available ICT facilities in the research institutes. Majority of the researchers were below 50 years, mostly males with higher educational achievements as most had the master and doctorate degrees. The study reported that majority of the researchers use ICT very frequently in the course of their work. It further revealed that researchers benefit immensely from the use of ICT facilities as they help in the dissemination of information.